Case Report: Facial nerve schwannoma: comprehensive surgical management with nerve reconstruction and hearing rehabilitation - Deffner, F.; Aschendorff, A.; Arndt, S.; Eisenhardt, S. U.; Hassepaß, F.; Ketterer, M. C. (Frontiers in Surgery, 2026)
Facial nerve schwannomas are rare tumors that pose diagnostic and surgical challenges. We report a 17-year-old female with progressive right-sided facial paresis initially misdiagnosed as Bell's palsy. MRI revealed a contrast-enhancing lesion of the facial nerve. She underwent a two-stage surgery: tumor resection via mastoidectomy and hearing rehabilitation, followed by facial nerve reconstruction using masseteric-to-facial nerve transfer and cross-face sural grafting. At nine months postoperatively, facial function improved from House-Brackmann grade V to III, and hearing was preserved. Early imaging and multidisciplinary management can enable complete tumor resection with functional restoration and favorable outcomes.